The immediate-early gene Egr-1 regulates the activity of the thymidine kinase promoter at the G0-to-G1 transition of the cell cycle. - Molnar, G (1994)
Production of thymidine kinase (TK) protein parallels the onset of DNA synthesis during the cell cycle. This process is regulated at transcriptional, posttranscriptional, and translational levels to cause a 40- to 50-fold increase in cytosolic enzymatic activity as cells progress from G1 to S phase. Transcriptional activation of the mouse TK gene through the cell cycle is dependent upon previously characterized cis elements of the proximal promoter, called MT1, MT2, and MT3, that bind at least two different complexes: TKE during the transition of cells from quiescence (G0) to G1, and Yi later at the G1/S boundary. To identify the transcription factors involved in this regulation, we screened a mouse fibroblast cDNA expression library with a labeled MT3 oligonucleotide probe and isolated a clone that encodes Egr-1, an immediate-early transcription factor, whose expression is regulated by serum or growth factors during the G0-to-G1 transition when cells reenter the cell cycle. Electrophoretic mobility shift assays demonstrate that Egr-1 is involved in the TKE complex that binds to the MT3 element and that expression of Egr-1 induces transcription of a mouse TK-chloramphenicol acetyltransferase reporter in transient transfections. These results suggest a role for Egr-1 in regulating expression of the TK gene at the G0-to-G1 transition.